Voices of the nation : women and public speech in nineteenth-century American literature and culture - Levander, Caroline Field, 1964- (Cambridge studies in American literature and culture, 1998)
Throughout the nineteenth century, American fiction displayed a fascination with women's speech - describing how women's voices sound and what reactions their speech produces, especially in their male listeners. Closer inspection of these recurring descriptions reveals that they also performed political work that has had a profound - though until now unspecified - impact on American culture. Caroline Leyander illustrates how commentaries on the female voice, propounded by such writers as Henry James, William Dean Howells, and Noah Webster, played a central role in attempts to define and enforce the radical social changes instituted by the emerging bourgeoisie. Levander also shows how nineteenth-century women authors depicted the female voice as a central theme in their novels and how these portrayals affected public speech.